Water wave diffraction by a cylinder array. Part 1. Regular waves - Ohl, C; Taylor, P; Borthwick, A (Cambridge University Press, 2001)
Diffraction of regular waves by arrays of vertical bottom-mounted circular cylinders is investigated using theoretical, computational, and experimental methods. Experiments in an offshore wave basin are designed to measure free surface elevation η at multiple locations in the vicinity of a multi-column structure subjected to regular waves of frequency 0.449